Block vs. Traditional Periodization of HIT: Two Different Paths to Success for the World’s Best Cross-Country Skier - Solli, Guro Strøm; Tønnessen, Espen; Sandbakk, Øyvind (Frontiers in Physiology, 2019)
In short-term studies, block periodization of high-intensity training (HIT) has been shown to be an effective strategy that enhances performance and related physiological factors. However, long-term studies and detailed investigations of macro, meso, and micro-periodization of HIT blocks in world-class endurance athletes are currently lacking. In a recent study, we showed that the world’s most successful cross-country (XC) skier used two different periodization models with success throughout her career. One including extensive use of HIT blocks, namely BP, and one using a traditional method namely TRAD. In this study, we compare BP with TRAD in two comparable successful seasons and provide a detailed description of the annual use of HIT blocks in BP. The participant is the most-decorated winter Olympian, with 8 Olympic gold medals, 18 world championship titles, and 114 world cup victories. Training data was categorized by training form (endurance, strength, and speed), intensity (low [LIT], moderate [MIT], and HIT), and mode (running, cycling, and skiing/roller skiing). No significant difference was found in the total endurance training load between BP and TRAD. However, training volume in BP was lower compared to TRAD (15±6 vs 18±7 h/wk, P=.001), mainly explained by less LIT (13±5 vs. 15±5 h/wk, P=.004). Lower volume of MIT was also performed in BP compared to TRAD (13 vs. 38 sessions/year), whereas the amount of HIT was higher in BP (157 vs. 77 sessions/year). While BP included high amounts of HIT already from the first preparation period, followed by a reduction towards the competition period, TRAD had a progressive increase in HIT towards the competition period. In BP, the athlete performed seven HIT blocks, varying from 7–11 days, each including 8–13 HIT sessions. This study provides novel insights into successful utilization of two different periodization models in the worlds best XC skier, and illustrates the macro, meso and micro- periodization of HIT blocks to increase the overall amount of HIT.